What are the senses of school? Real and fictional perspectives on (dis)obediences in schooling (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Review of the book Qualquer semelhança não é mera coincidência: um olhar para a escola a partir do teatro [Any resemblance is not mere coincidence: a look at the school through the lens of theater] by Jean Carlos Gonçalves. This work is part of the desEducar Collection, published by Hucitec Editora. The book inaugurates a fifteen-year period between the author’s thesis defense and his revisitation of the research. It includes a preface, an introduction, an introductory note, and a prologue, followed by three acts that convey the dialogues between theater and school, with their statements and concepts portrayed in enunciative-discursive materialities in the form of theatrical exercises. This is followed by an epilogue and a section dedicated to school memories.
Keywords: school; theater; language; Bakhtin